What's in a word?. (2nd April 2022) - Freeman, Helen
Abstract : In this special issue on communication, language and literacy, Helen Freeman talks about the 2021 Oxford Children's Word of the Year and shares some insight on Oxford's latest Children's Language Report, highlighting the role that early years practitioners can play to help children develop the vocabulary they need to thrive.